School-Immigrant Family-Community Collaboration Practices: Similarities and Differences - Boulaamane, Khaoula; Bouchamma, Yamina (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2021)
We compared school-immigrant family-community collaboration practices based on the six dimensions of Epstein’s influence model (2001). These three groups of stakeholders (N = 54) participated in this study by answering a questionnaire on their collaboration practices. Kruskall-Wallis analyses revealed a notable difference between the three groups with regard to decision-making practices and at-home learning. A positive correlation was found between the number of years of teaching experience in the school and communication, volunteering, parenting, and decision making, as well as between the child’s grade level and parenting. Results show that although the collaboration practices followed Epstein’s involvement theory, they remained weak, with no significant difference between the three groups in terms of their use. Our findings are discussed in light of recent literature and their practical implications and avenues for future research are proposed to better understand and improve the conditions favoring school-immigrant family-community collaboration.